Towards interest-free banking - Ahmad, Mahmud, Shaikh (New Delhi : Kitabbhavan, 2000)
Presentation on how to evolve a banking structure in Islamic economics.
Includes index.
Includes bibliographical references.
Keywords: Banks and banking -- Religious aspects -- Islam